Immunotoxicity of Perfluorooctanoic Acid to the Marine Bivalve Species Ruditapes philippinarum. (18th January 2022) - Li, Fengling; Liu, Zhiyu; Yao, Lin; Jiang, Yanhua; Qu, Meng; Yu, Yongxing; Gong, Xiuqiong; Tan, Zhijun; Li, Zhaojie
Abstract: Polyfluorinated alkylated substances are recognized as an important class of pollutants in marine environments. Bivalves are good model organisms for evaluating the toxicity of pollutants and monitoring marine environments. In the present study, immunotoxicity of perfluorooctanoic acid (PFOA) was investigated by measuring biomarkers of the immune profile of Ruditapes philippinarum . In bivalves, hemocytes are an important component of the immune system. Thus, hemocyte proliferation, phagocytosis, cell viability, and immune enzyme activities, which have been applied as marine pollution bioindicators, were identified and observed for changes after exposure to PFOA in R. philippinarum . Based on the integrated biomarker responses method, we selected five biomarkers to evaluate PFOA risk at the multibiomarker level. In addition, the histopathological alterations of hemocytes in bivalves were used as indexes of the response to environmental stress. The subcellular structure of the hemocytes in R. philippinarum changed significantly with PFOA exposure, including hemocyte and nucleus morphological changes, organelle dissolution, cytomembrane and karyotheca swelling, and cytoplasm vacuolization. The present study verifies PFOA immunotoxicity to R. philippinarum at different levels and the integrated assessment of stress levels caused by PFOA in marine environment. Our results will provide new insights into evaluating adverse effects of PFOA and monitoring marine ecosystem. Environ Toxicol Chem 2022;41:426–436. © 2021 SETAC